A lattice-based approach for chemical structural retrieval. (March 2015) - Tang, Peng; Hui, Siu Cheung; Fong, Alvis C.M.
Abstract: Searching for chemical structures with similar structural and functional information of organic chemicals is an important part of the drug discovery process. However, the current chemical structural retrieval methods have focused mainly on finding chemicals with similar structures to the input chemical structural query, and tend to ignore the functional features which are important for determining the chemical property and activity of the chemicals. In this paper, we propose a lattice-based approach for chemical structural retrieval. The proposed lattice-based approach is based on Formal Concept Analysis. It retrieves chemical structures that have functional groups and interactions between functional groups similar to the chemical structural query. The performance of the proposed lattice-based approach is evaluated and its promising performance results have shown that the proposed approach is effective for chemical structural retrieval.